Farm-nonfarm growth linkages in Zambia - Hazell, Peter B. R.; Hojjati, Behjat (International Food Policy Research Institute, 1995)
This paper uses farm survey data from Eastern Province, Zambia to show that regional income multipliers arising from agricultural growth may be stronger than previously thought for Sub-Saharan Africa. However, the growth multipliers are driven primarily by household consumption demands, and they arise largely within the agricultural sector itself because of strong marginal budget shares for nontradable foods. Policies and investments to promote the supply response and local marketing of nontradable foods could greatly enhance the income and employment impacts of agricultural growth.